SWOT ANALYSIS AS A BASIS OF STRATEGY IN EFFORTS TO INCREASE THE NUMBER OF PATIENT VISITS AT ABC HOSPITAL PAIN MANAGEMENT CLINIC - Evy Ekantiana; Puji Swastika Sari; Lita Bestari; Wiwiek Handayani; Reimond Hasangapan Mikkael (Jurnal Ekonomi, 2023)
Patient visits to ABC Hospital Pain Management Clinic before the pandemic: 181 per year, during the 2021 pandemic: 54 visits per year and in 2022: 90 visits, this is not in accordance with the set visit target. This type of research used is qualitative. The marketing strategy to increase the number of patients uses a SWOT analysis where the company is in quadrant 3 where the strategy used is a defensive strategy and is in cell 5 with a concentration strategy of growth through horizontal integration and stability, where the company does not make changes. The results of the strategic research carried out are making a practice schedule, online registration, determining a permanent practice room; improve teleconsul services, promote programs through social media and local media, create pain patient communities and program events or gatherings,